RETRACTED: Synthesis of Bioactive Yttrium-Metal–Organic Framework as Efficient Nanocatalyst in Synthesis of Novel Pyrazolopyranopyrimidine Derivatives and Evaluation of Anticancer Activity - Saleh, Raed Obaid; Achmad, Harun; Daminov, Botir Turgunpulatovich; Kzar, Hamzah H.; Mahdi, Ahmed B.; Hammid, Ali Thaeer; Abid, Mohammed Kadhem; Opulencia, Maria Jade Catalan; Mustafa, Yasser Fakri; Sharma, Himanshu (Frontiers in Chemistry, 2022)
Novel Yttrium-metal–organic framework (Y-MOF) was synthesized under optimal conditions of microwave with a power of 20 W, the temperature of 30 degrees of centigrade, and time duration of 10 min. The products were characterized by SEM (morphology and size distribution), TGA (thermal stability), BET technique (surface area), and FTIR (characterization of the related group). The Yttrium-metal–organic framework (Y-MOF) synthesized in this study, after identifying and confirming the structure, was used as an efficient and recyclable catalyst in the synthesis of new pyrazolopyranopyrimidine derivatives. Following the study of the properties and applications of Y-MOF, its anticancer properties on breast cancer cells based on the MTT method were evaluated, and significant results were observed. In addition, the anticancer properties of the pyrazolopyranopyrimidine derivatives were investigated.